IMPLEMENTASI SISTEM INFORMASI WARGA BERBASIS WEB MENGGUNAKAN OPENSID DI DESA CIGOONG UTARA, KECAMATAN CIKULUR, KABUPATEN LEBAK - Ade Fauji; Ahmad Ghifari; Rian Ristiawan (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
Along with the development of technological advances, the need for fast, accurate, easy and practical data processing has become a demand, so that currently the majority of institutions have utilized a computerized data management system. No exception for data management in village government institutions, each village is required to provide the best service to the community in the field of letter making, tax payments, population data collection and other needs related to village office services. But most of the service process is still done conventionally. Therefore, the author recommends a web-based public service application to be implemented in North Cigoong Village. This village service application is made web-based that can be used online, so village people can enjoy village services more quickly and easily. It is hoped that with the application of this village service, it can improve the quality of the service process to the people of North Cigoong village